Challenges in Managing Portal Hypertension and Fibrosis in a Case of Biliary Atresia Post-Kasai Procedure—Implications for Early Detection and Long-Term Care - Jasin, Yayu Dwinita; Prihaningtyas, Rendi Aji; Octariyandra, Syania Mega; Setyoboedi, Bagus; Arief, Sjamsul (Universitas Airlangga, 2025)
Biliary atresia frequently causes portal hypertension, resulting in significant morbidity and mortality. Elevated portal pressure can be detected as early as during a Kasai procedure. Pediatric portal hypertension is the primary cause of various complications, including variceal hemorrhage, ascites, and extra-hepatic processes. This paper aims to draw attention to the complications and limitations of the Kasai procedure by presenting a case of portal hypertension and fibrosis in an 8-month-old male infant with biliary atresia who underwent the procedure at 3 months. The patient was never completely free of jaundice post-surgery. The jaundice worsened, and the pale-colored stool reappeared two months later. The abdomen was distended, accompanied by ascites, hepatomegaly, splenomegaly, and dilated veins. Edema was present on the lower extremities and the scrotum. The patient was diagnosed with biliary atresia and portal hypertension. Supportive therapy was recommended as a preparatory measure before a liver transplant. However, the parents declined the procedure due to financial constraints. This case suggests that the Kasai procedure may not always be effective. Despite the timely execution of the procedure, liver fibrosis may persist and be associated with portal hypertension. Most patients develop significant fibrosis that progresses to cirrhosis, requiring a liver transplant. To date, biliary atresia remains the primary indication for liver transplant in children, with no alternative medical treatment recognized. This case report highlights the progression of portal hypertension and liver fibrosis following the Kasai procedure for biliary atresia, emphasizing the challenges in early detection, complications management, and the exploration of alternative therapeutic strategies. Highlights: 1. This study critically reviews the limitations and complications of the Kasai procedure in treating biliary atresia, with particular focus on portal hypertension issues, for which case reports are limited. 2. This study highlights the important need for accessible and effective long-term treatment alternatives by presenting a pediatric case where financial constraints prevented a liver transplant. 3. The data from this study are anticipated to contribute to the advancement of healthcare equity and pediatric liver disease management.